18F-Fluoride Signal Amplification Identifies Microcalcifications Associated With Atherosclerotic Plaque Instability in Positron Emission Tomography/Computed Tomography Images. (January 2019) - Creager, Michael D.; Hohl, Tobias; Hutcheson, Joshua D.; Moss, Alastair J.; Schlotter, Florian; Blaser, Mark C.; Park, Mi-Ae; Lee, Lang Ho; Singh, Sasha A.; Alcaide-Corral, Carlos J.; Tavares, Adriana A.S.; Newby, David E.; et al.
Abstract : Background: Microcalcifications in atherosclerotic plaques are destabilizing, predict adverse cardiovascular events, and are associated with increased morbidity and mortality. 18 F-fluoride positron emission tomography (PET)/computed tomography (CT) imaging has demonstrated promise as a useful clinical diagnostic tool in identifying high-risk plaques; however, there is confusion as to the underlying mechanism of signal amplification seen in PET-positive, CT-negative image regions. This study tested the hypothesis that 18 F-fluoride PET/CT can identify early microcalcifications. Methods: 18 F-fluoride signal amplification derived from microcalcifications was validated against near-infrared fluorescence molecular imaging and histology using an in vitro 3-dimensional hydrogel collagen platform, ex vivo human specimens, and a mouse model of atherosclerosis. Results: Microcalcification size correlated inversely with collagen concentration. The 18 F-fluoride ligand bound to microcalcifications formed by calcifying vascular smooth muscle cell derived extracellular vesicles in the in vitro 3-dimensional collagen system and exhibited an increasing signal with an increase in collagen concentration (0.25 mg/mL collagen −33.8×10 2 ±12.4×10 2 counts per minute; 0.5 mg/mL collagen −67.7×10 2 ±37.4×10 2 counts per minute; P =0.0014), suggesting amplification of the PET signal by smaller microcalcifications. We further incubated human atherosclerotic endarterectomy specimens with clinically relevant concentrations of 18 F-fluoride. The 18 F-fluoride ligand labeled microcalcifications in PET-positive, CT-negative regions of explanted human specimens as evidenced by 18 F-fluoride PET/CT imaging, near-infrared fluorescence, and histological analysis. Additionally, the 18 F-fluoride ligand identified micro and macrocalcifications in atherosclerotic aortas obtained from low-density lipoprotein receptor-deficient mice. Conclusions: Our results suggest that 18 F-fluoride PET signal in PET-positive, CT-negative regions of human atherosclerotic plaques is the result of developing microcalcifications, and high surface area in regions of small microcalcifications may amplify PET signal. Abstract : Supplemental Digital Content is available in the text.